Financial Reform and Development in the Philippines, 1980-1997: Imperatives, Performance and Challenges - Gilberto M. Llanto; Ponciano Jr. S. Intal (Philippine Institute for Development Studies (PIDS), 1998)
The recent currency and financial turmoil in East Asia have led to the evaluation of current financial and macroeconomic policies. The Philippines, which has been the worst hit in the 1980 economic crisis has indicated greater resilience in the 1990 financial crisis. Experts have attributed this to the institutional reforms the country undertook during the past 15 years. This paper discusses the reform and development the Philippine government undertook during that period with a focus in the financial system. This also identifies the challenges facing the sector in the light of greater international financial integration. Analysis indicates that the achievement of financial sector stability requires prudential regulation and stable macroeconomic environment. Recommendations regarding regulation, supervision and monitoring in the sector are hoped to aid policymakers in their future endeavors.
Keywords: 330; financial market; financial economy; financial sector; financial reform; financial liberalization; financial integration; prudential regulation